Anaerobic Digestion of Pretreated Industrial Residues and Their Energetic Process Integration - Bochmann, Günther; Pesta, Gunther; Rachbauer, Lydia; Gabauer, Wolfgang (Frontiers in Bioengineering and Biotechnology, 2020)
The Food and Beverage industry offers a wide range of organic feedstock to use for biogas production by means of anaerobic digestion (AD). Microorganisms convert organic compounds, solid, pastry or liquid ones, within four steps to biogas which mainly consists of CH4 and CO2. Therefore, various technologies are available and worldwide several examples exist, which shows the implementation of such technologies on site. The food and beverage industry offers a huge potential of using this technologies due to their amount of residues and their requirement for heat and power at the same time. In the following study we analyze specific industries regarding their implementation potential based on waste occurring and heat and power demand. Due to their chemical composition several feedstock are stubborn against microbiological degradation. Physical, chemical, microbiological and combination of these are used to increase the biological availability of the feedstock. In the following examples will be discussed implementing AD technology in industrial processes. As examples the brewery industry, dairies, slaughter houses, sugar industry and sugar industry.